2014
DOI: 10.1159/000357066
|View full text |Cite
|
Sign up to set email alerts
|

Complication Rate of Endosonography (Endobronchial and Endoscopic Ultrasound): A Systematic Review

Abstract: Background: Endosonography [endoscopic ultrasound (EUS)-guided fine needle aspiration and endobronchial ultrasound (EBUS)-guided transbronchial needle aspiration] is increasingly used for lung cancer staging and the assessment of sarcoidosis. Serious adverse events (SAE) have been reported in case reports, but the true incidence of complications is yet unknown. Objectives: To assess the rate of SAE related to endosonography and to investigate associated risk factors. Materials and Methods: PubMed, EMBASE and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
112
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(126 citation statements)
references
References 35 publications
5
112
1
8
Order By: Relevance
“…To the best of our knowledge, there are 2 systematic reviews and 2 Japanese survey studies in the literature describing the serious complications associated with EBUS-TBNA. 2,4,12,14 The serious complication rate of EBUS-TBNA was determined to be 0.16% in the present study.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…To the best of our knowledge, there are 2 systematic reviews and 2 Japanese survey studies in the literature describing the serious complications associated with EBUS-TBNA. 2,4,12,14 The serious complication rate of EBUS-TBNA was determined to be 0.16% in the present study.…”
Section: Discussionmentioning
confidence: 47%
“…The serious complication rate of endoscopic ultrasonography and convex-probe EBUS-TBNA was reported as 0.14% in the systematic review of von Bartheld et al 14 They reported 5 serious adverse events, consisting of 2 infectious complications, 2 pneumothorax, and 1 airway edema and hypoxemia, in 9,119 EBUS-performed cases (0.05%). There is no mortality reported either in this review or in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…En nuestra serie no reportamos complicaciones asociadas al procedimiento. Dentro de las complicaciones reportadas en la literatura se describe el sangrado auto limitado el más frecuente, con tasas reportadas menores a 5% de los procedimientos mientras que la tasa de neumotó-rax es de 1% y sin presentar eventos fatales, similar a lo encontrado en nuestra serie 14,15 .…”
Section: Discussionunclassified